Undang-undang Merek No.15 Tahun 2001 - Widjaja, Gunawan (Pelita Harapan University, 2001)
Regulations pertaining Trade Mark and Trade Seivice have been changed for several Â times. The first amendment broke the First to Use system of Mark registration onto the First to Register. The second amendment made in 1997 to Law No.19 Year 1992, by Law No.14 Year 1997, has already considered the participation of Indonesia in tlw Agreement Establishing the World Trade Organization. Again today based on the same consideration (the participation of Indonesia in the Agreement Establishing the World Trade Organization), Indonesia issued new law pertaining the Mark with Law No. 15 Year 2001. If we read through the fio.15 Year 2001, we could find that actually there are at least nine changes and amendments. Among them two matters are really new for Indonesian legal syatem, i.e. the using of Commercial Court as the only Court having authority to handle settlement of Mark disputes (beside arbitration); and the introduction of Provisional Measures introduced in Article 50 TRIPs. This paper will elaborate the used of Commercial Court in settling Mark disputes, and provide basic knowledge of Provisional Measures as stipulated in Article 85 to Article 88 of Law No.15 Year 2001.Â